Long-Term Efficacy of Various Natural or “Green” Insecticides against Bed Bugs: A Double-Blind Study - Jerome Goddard (Insects, 2014)
Bed bugs are resurging throughout the world, and, thus, effective pest control strategies are constantly needed. A few studies have evaluated 25(b) and other natural, or so-called “green” products, as well as over-the-counter insecticides for bed bugs, but additional studies are needed to determine efficacy of bed bug control products. This double-blinded research project was initiated to examine long-term effectiveness of six commercially available natural or “green” insecticides against bed bugs and to compare them with three known traditional residual products. Water was used as a control. Products were evaluated against both susceptible and resistant strains of bed bugs (1200 bugs each), and two different substrates were used. Temprid® (Bayer Corporation, Monheim, Germany), Transport® (FMC Corp., Philadelphia, PA, USA), Invader® (FMC Corporation, Philadelphia, PA USA), Cimexa® (Rockwell Laboratories, Kansas City, MO, USA), and BBT-2000® (Swepe-Tite LLC, Tupelo, MS, USA) were the only products which showed any substantial (>40%) bed bug control upon exposure to treated substrates after the six-month waiting period, although results with the resistant bed bug strain were much reduced. Alpine dust® (BASF Corporation, Florham Park, NJ, USA) killed 27% of bed bugs or less, depending on strain and substrate. EcoRaider® (North Bergen, NJ, USA) and Mother Earth D® (Whitmire Microgen, Florham Park, NJ, USA) (diatomaceous earth) produced 11% control or less. Cimi-Shield Protect® (Pest Barrier, Carson, CA, USA) showed no activity against bed bugs in this study. Analysis using SAS software showed a three-way interaction between treatment, substrate, and bed bug strain (Numerator DF 9; Denominator DF 80; F = 4.90; p < 0.0001).